Routledge handbook of risk management and the law - Suveiu, Virginia A. (New York Routledge, 2023)
In today's highly globalized and regulated economy, private and public organizations face a complex myriad of laws and regulations. A process designed to detect and prevent regulatory compliance failures is vital. However, such an effective process cannot succeed without development and maintenance of a strong compliance and legal risk management culture. This wide-ranging handbook pulls together work from experts across universities and industries around the world in a variety of key disciplines such as law, management, and business ethics. It provides an all-inclusive resource, specifying everything that needs to be known in these developing areas. With no single text currently available, the book fills a gap in our current understanding of legal risk management, regulatory compliance, and ethics, offering the potential to advance research efforts and enhance our approaches to effective legal management practices. Edited by an expert on legal risk management, this book is an essential reference for students, researchers, and professionals with an interest in business law, risk management, strategic management, and business ethics"--
Introduction / Patricia Lee-Gulley and Virginia A. Suveiu -- Operational risk management / Tim East -- Compliance, corporate governance, and corporate social responsibility : Part I - the interplay between the company, the stakeholder and the regulators / Marcia Weldon and Lauren Miller -- Compliance, corporate governance, and corporate social responsibility : Part II - the interplay between the company, the stakeholder, and shareholders / Marcia Weldon and Christyne Vachon -- Understanding and managing behavioral ethics risk / Todd Haugh -- Deconstructing risk - practical understanding and perspectives / Kevin Meredith -- Fostering dialog about the future of law as risk and compliance are coming into their own / Virginia A. Suveiu -- Insurance : a look inside the Claims Department / Joyce Segelken -- Contract risk management within an operational context / James N. Phillips Jr. -- Contract risk and uncertainty management / Don Shannon -- Finding opportunities in risk for small businesses and subcontractors / Linda Harris -- Supply chain risk management considerations in an ever-changing world / Jessie Castro -- Operationalizing compliance : best practices / Tom Fox -- Internal investigations / Michael Volkov, Matt Stankiewicz and Noah Smith -- Human resources considerations / Silvia Van Dusen -- The self-regulatory organization's role in promoting ethical behavior in industry / Laura McNamire -- Risk and compliance considerations in the startup world / Cynthia Fascenelli Kirkeby -- Corporate compliance and ethics challenges, a European perspective / Claudiu Jipescu-Munteanu -- Financial considerations, a global perspective / Philip Wood -- Considerations for a successful cybersecurity program / Kristine A. Hayes Munson -- Value and risk in the fourth informational revolution / Peter Coffee -- The convergence of social media, technology and data / Jeff Koller -- Records management/records retention risk considerations / Patricia Lee-Gulley and John Drudi -- Quality management considerations / Shep Bentley -- Data privacy considerations, an international viewpoint / Marius Magureanu -- Intellectual property considerations and business risk in China / Roger Phillips -- Environmental compliance risk management / Amber Baylor -- Compliance leadership / Don Polden -- Ethics and leadership / LaSharnda Beckwith -- Risk and innovation / Kevin Meredith -- Uncertainty management / Chris Guzelian -- A view from the top / Cynthia Patton.
Includes bibliographical references and index.
Keywords: Corporate governance -- Law and legislation -- United States; Risk management -- Law and legislation -- United States